Application of Whole Exome Sequencing in Mutational Analysis of Patients with Ohtahara Syndrome - Thi Quynh Mai, Nguyen; Le Trung Hieu, Nguyen; Thi Khanh Van, Le; Thuy Minh Thu, Nguyen; Tran Anh Ngan, Le; Thi Dieu Hien, Huynh; Thi Thu Hang, Do (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 38 No 2, 2022)
Ohtahara syndrome is one of the earliest and most severe forms of developmental and epileptic encephalopathy. Over the last decade, the rapid advances in molecular techniques, especially in high-throughput sequencing (HTS), have revealed that a majority of Ohtahara patients have genetic etiology. About 20 genes have been found to be related to this syndrome so far, and Next Generation Sequencing (NGS) technique is now an important genetic test for this syndrome. This study was conducted on 4 patients with Ohtahara syndrome referred to Children’s Hospital 2, Ho Chi Minh City. Whole-exome sequencing (WES) following targeted analysis on 283 epileptic encephalopathy–related genes was performed to identify disease-causing variants of the patients. Following multi-step bioinformatics analysis, trio-based Sanger sequencing confirmation, and variant classification according to standards of The American College of Medical Genetics and Genomics – 2015, we have identified 2 pathogenic mutations in 2 patients: OH3 ( KCNQ2 , c.868G>A, p.G290S) and OH4 ( SCN2A , c.788C>T, p.A263V). The results of this study contribute to verifying the role of genetic factors in Ohtahara syndrome in Vietnamese patients. This study also confirms that NGS in general and WES, in particular, are reliable and useful in detecting genetic causes of Ohtahara syndrome, thereby, assisting in diagnosis and treatment of this syndrome.